2006
DOI: 10.3168/jds.s0022-0302(06)72373-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, Bovine Somatotropin, and Dietary n-3 Fatty Acids in Lactating Dairy Cows: I. Ovarian, Conceptus, and Growth Hormone–Insulin-Like Growth Factor System Responses

Abstract: The objective was to examine effects of bovine somatotropin (bST), pregnancy, and dietary fatty acids on reproductive responses in lactating dairy cows. Beginning at approximately 17 d in milk (DIM), a comparison was made of isoenergetic diets comprising supplementary lipids of whole cottonseed vs. calcium salts of fish oil enriched lipid (FO). Ovulation was synchronized in cows with a presynchronization plus Ovsynch protocol, and cows were inseminated artificially by appointment or not inseminated (d 0 = time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 25 publications
6
52
3
3
Order By: Relevance
“…Some authors reported an improved increased follicular and corpus luteum growth , oocyte (Moallem et al, 2013;Zachut et al, 2010) and embryo quality (Thangavelu et al, 2007), decreased pregnancy loss (Ambrose et al, 2006), reduced plasma prostaglandin (Petit et al, 2002), and increased serum progesterone concentration (Jahani-Moghadam et al, 2015), reduced interval from calving to ovulation (Colazo et al, 2009). In contrast, others noted no changes in milk progesterone concentration or corpus luteum activity (Ponter et al, 2006), or oocyte quality (Bilby et al, 2006, Fouladi-Nashta et al, 2009. The inconsistencies among these studies could be due to differences in the amounts of lipid supplements, duration of supplementation, and season.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 95%
“…Some authors reported an improved increased follicular and corpus luteum growth , oocyte (Moallem et al, 2013;Zachut et al, 2010) and embryo quality (Thangavelu et al, 2007), decreased pregnancy loss (Ambrose et al, 2006), reduced plasma prostaglandin (Petit et al, 2002), and increased serum progesterone concentration (Jahani-Moghadam et al, 2015), reduced interval from calving to ovulation (Colazo et al, 2009). In contrast, others noted no changes in milk progesterone concentration or corpus luteum activity (Ponter et al, 2006), or oocyte quality (Bilby et al, 2006, Fouladi-Nashta et al, 2009. The inconsistencies among these studies could be due to differences in the amounts of lipid supplements, duration of supplementation, and season.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 95%
“…Decreased progesterone concentration in the early luteal phase in cattle has been shown to reduce embryo survival (Mann et al, 1998). However, supplementing diets with fish meal (Mattos et al, 2002) or fish oil (Bilby et al, 2006) has not been shown to change luteal progesterone production in cows. In pigs, supplementing sow diets with fish oil, rich in EPA and DHA, did not affect circulating progesterone levels 60 to 72 h after ovulation (Smit et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research has focused on decreasing the ratio of dietary n‐6 to n‐3 fatty acids (FA) (Bilby et al . ) because of the health benefits of lower ratios (Simopoulos ). The regulatory roles of these two FA groups on animal reproduction and the underlying mechanisms were discussed earlier (Mattos et al .…”
Section: Introductionmentioning
confidence: 99%